INVESTIGATION OF SITUATIONAL - PEDAGOGICAL FACTORS AFFECTING SPEAKING RELUCTANCE AMONG UNIVERSITY EFL STUDENTS - Abdolnoor Khaleghi (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
In second and foreign language acquisition, a number of factors appear to contribute to predisposing one learner to seek and another learner to avoid L2 communication. It is also believed that speaking as a means of oral participation in university EFL classrooms is an anxiety-provoking phenomenon. Some factors make students be reluctant to use L2 in speaking settings. It may be regarded as the most challenging concern that instructors are recently facing in EFL classes. Consequently, this study was conducted to investigate the underlying factors affecting speaking reluctance among university students and to suggest solutions to this problematic issue. Data were gathered through an informal 12-items Likert-scale questionnaire and a semi-structured interview. The results indicated that several situational factors (instructors’ behavior, class atmosphere and topic selection) and pedagogical factor (teaching style, instructor-student relationship, course materials, educational system and low English proficiency) cause students’ speaking reluctance in academic EFL settings.